The function of glutaredoxin GRXS15 is required for lipoyl-dependent dehydrogenases in mitochondria - Moseler, Anna Maria; Kruse, Inga; Maclean, Andrew E.; Pedroletti, Luca; Franceschetti, Marina; Wagner, Stephan; Wehler, Regina; Fischer-Schrader, Katrin; Poschet, Gernot; Wirtz, Markus; Dörmann, Peter; Hildebrandt, Tatjana M.; et al. (Plant physiology, 2021)
Decreased activity of the mitochondrial glutaredoxin GRXS15 causes metabolic defects associated with impaired lipoyl cofactor-dependent dehydrogenase complexes.
Gesehen am 28.10.2021